Strategi Manajemen Risiko Pembiayaan Murabahah Studi Kasus di BTN Syariah Yogyakarta - Sumar'in, Sumar'in; Juliansyah, Juliansyah (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2016)
Awareness of the risks are well understood is an integral part of efforts to optimize the benefits of a business, especially in the business in the financial sector. The purpose of this study was to determine the risk management and strategies to deal with it in a murabaha financing in BTN Syariah Yogyakarta. Qualitative approach used in this study. While the data obtained through interviews, observation, and documentation. The results showed that the management of risk in murabahah financing in BTN Syariah Yogyakarta must be doing by minimize the risk that happening, either ona precontractand postcontract. Mitigation pre-contract is done in compliance with Standard Operating Procedureset of internal bank, do selecting to mudharib’s candidate, and feasibility analysis mudharib’s candidate. While mitigating the risk of post-contract is used a standard system with computer technology with sigma program